PENGEMBANGAN KARAKTER RELIGIUS PESERTA DIDIK MELALUI PEMBELAJARAN KIMIA MATERI HIDROKARBON SMK - Ningrum, Lis Setiyo; Supardi, Kasmadi Imam; Jumaeri, Jumaeri; Haryani, Sri (Jurnal Inovasi Pendidikan Kimia, 2020)
In order to create the next generation of people with character, religious values really need to be instilled in students. One of them is by integrating religious values in learning material. Integrating this aspect can show positive changes to face global competition in the era of 4.0. This study aims to develop a questionnaire instrument for measuring the religious character of students integrated in chemistry learning. The research design used is R & D (Research and Development) research. The development model used is a modified 4-D model as suggested by Thiagarajan, Semmel and Semmel which consists of define, design, develop and disseminate. Based on the results of this study, it can be concluded that this study produced a questionnaire instrument for measuring students' character in chemistry learning consisting of 20 indicators that were declared valid and reliable with a validity price of 0.9028 and a reliability of 0.9037. The questionnaire instrument was developed by integrating religious character values with the learning of hydrocarbon chemistry. The results showed that the questionnaire instrument was effective for measuring the religious character of students with an average increase in the religious character of students by 0.54 so that it was included in the medium category.